The effect of invertase concentration on quality parameters of fondant - Ozcan, Ozge; Yildirim, Rusen Metin; Toker, Omer Said; Akbas, Nurcanan; Ozulku, Gorkem; Yaman, Mustafa (SPRINGER INDIA, 2019)
Fondant is a saturated sugar solution which is a paste- or cream-like heterogeneous system consisting of a solid phase (saccharose crystals), a liquid phase (saturated saccharose solution and glucose/invert sugar) and a gaseous phase. Fondant is used as a filling material and as a coating material for pastry, confectionery and chocolate products. Therefore, mechanical properties are important for both machinability and sensory properties of the fondant. In the present study, the invertase enzyme was added at different concentrations (0.1-0.5%) to investigate its effect on the textural and rheological properties of the fondant during the storage period as well as on the sugar composition. After the first week of storage, the hardness of the control sample decreased from the initial value of 221.1-69.24 g and 48.22 g for the addition of 0.1 and 0.5% enzyme. G ' and G '' values of the fondant decreased by treatment with invertase enzyme. The positive effect of the invertase addition to fondant was also perceived in sensory evaluation. Therefore, using invertase enzyme enabled the product having desired quality characteristics. The results of the present study highlighted that invertase enzyme can be used to soften the product improving the sensory characteristics and machinability and reducing or eliminating the crystallization of sucrose which negatively affects the quality parameters. Depending on the intended purpose of the fondant, the invertase concentration can be optimized.
Keywords: Confectionery; Fondant; Rheology; Texture; Enzyme; CRYSTALLIZATION; MOISTURE; BEHAVIOR; SUGAR; Food Science & Technology